Genetic Screening of Mutations Associated with Fabry Disease in a Nationwide Cohort of Juvenile Idiopathic Arthritis Patients - Gonçalves, Maria J.; Mourão, Ana F.; Martinho, António; Simões, Olívia; Melo-Gomes, José; Salgado, Manuel; Estanqueiro, Paula; Ribeiro, Célia; Brito, Iva; Fonseca, João E.; Canhão, Helena (Frontiers in Medicine, 2017)
Fabry’s disease (FD) is a lysosomal storage disorder associated with an alpha-galactosidase A deficiency. The prevalence of Fabry’s disease among juvenile idiopathic arthritis (JIA) patients with established diagnosis is unknown, but as musculoskeletal pain may be an important complaint at presentation, misdiagnosed cases are anticipated. With this study, we aim to calculate the frequency of FD associated mutations in a cohort of JIA patients. Children with JIA from a national cohort were selected. Clinical and laboratorial information was recorded in the Portuguese rheumatic diseases register (Reuma.pt). Molecular genetic testing to detect GLA gene mutations was performed. After the multiplex PCR technique for DNA amplification, direct sequencing of the complete sequence of GLA gene was completed. From a cohort of 292 patients with JIA (188 female, 104 male), mutations were identified in 5 patients (all female). Four patients had the mutation D313Y, a rare GLA variant, which is associated with low enzymatic levels in plasma, but normal lysosomal levels. One patient presented the missense mutation R118C, which was previously described in Mediterranean patients with FD. This is the first screening of Fabry’s disease mutations in a cohort of JIA patients. No “classic” pathogenic Fabry’s disease mutations were reported. The late-onset Fabry’s disease associated mutation, R118C, was found in a frequency of 0,34% (1/292).